Utilization of Digital Cash Book Applications as an Effort to Improve Business Performance - Misrah, Misrah; Kurnia M, Fakhruddin (Celebes Journal of Community Services, 2024)
The utilization of digital ledger applications as an effort to enhance business performance has a positive and comprehensive impact on various operational and strategic aspects of the company. These applications not only simplify the recording of financial transactions but also improve accuracy, efficiency, and visibility into the company's financial condition. The implementation of digital ledger applications not only creates a more efficient work environment but also supports companies in facing dynamic business challenges. With careful monitoring, continuous training, and proper integration, companies can continuously maximize the benefits of this technology to achieve sustainable business growth. The results of community service activities (PKM) indicate that the perception of Bone Village Government staff towards the utilization of digital ledger applications significantly influences daily life and business improvement.